2023
DOI: 10.1002/adfm.202210233
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Production of Highly Functional Vascularized Hepatobiliary Organoids from Human Pluripotent Stem Cells using a Scalable Microfluidic Platform

Abstract: Abstract“Organoid medicine” has rapidly progressed over the past decade as a new class of therapeutics with high functionality and complexity for addressing unmet medical needs such as effective treatment of patients suffering from chronic liver disease using liver organoids. Here, scalable and xeno‐free integrated differentiation platforms are established to generate hepatic progenitors, mesenchymal stromal cells, and endothelial cells using individual human pluripotent stem cell lines as starting cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“… Blackford et al (2023) reported that HLCs cultured on soft polyethylene glycol (2.5%) secreted more ALB than PHHs and metabolized more urea than HLCs cultured in alginate ( Blackford et al, 2023 ), underscoring the potential of synthetic polymers for bioprinting. Additionally, Abbasalizadeh et al (2023) achieved a high yield of hiPSC-derived hepatic organoids by combining PEG microencapsulation and microfluidic systems, paving the way for cell transplantation ( Abbasalizadeh et al, 2023 ).…”
Section: Hipsc-derived Hepatocytes For Bioprintingmentioning
confidence: 99%
“… Blackford et al (2023) reported that HLCs cultured on soft polyethylene glycol (2.5%) secreted more ALB than PHHs and metabolized more urea than HLCs cultured in alginate ( Blackford et al, 2023 ), underscoring the potential of synthetic polymers for bioprinting. Additionally, Abbasalizadeh et al (2023) achieved a high yield of hiPSC-derived hepatic organoids by combining PEG microencapsulation and microfluidic systems, paving the way for cell transplantation ( Abbasalizadeh et al, 2023 ).…”
Section: Hipsc-derived Hepatocytes For Bioprintingmentioning
confidence: 99%
“…5,6 A variety of intelligent hydrogels have been extensively studied in order to explore their potential use as controlled medication delivery systems. 7,8 These smart stimuliresponsive materials vary their volume in response to external factors like pH, 9−12 temperature, 13,14 magnetic field, 15,16 etc. Smart materials have performed well in controlled drug release and site-specific delivery studies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrogels are a category of polymer networks that exhibit three-dimensional structures and possess hydrophilic properties . These materials have gained significant traction in various domains, including biomedicine and environmental research, due to their versatile uses. Hydrogels exhibiting distinct responses based on various stimuli, including temperature, pH, light, and electric or magnetic fields, are classified as “smart” hydrogels. , A variety of intelligent hydrogels have been extensively studied in order to explore their potential use as controlled medication delivery systems. , These smart stimuli-responsive materials vary their volume in response to external factors like pH, temperature, , magnetic field, , etc. Smart materials have performed well in controlled drug release and site-specific delivery studies.…”
Section: Introductionmentioning
confidence: 99%
“…2D HEAs show remarkable catalytic performance in various catalytic reactions due to their four "core effects," namely, high-entropy effect, lattice distortion effect, hysteresis diffusion effect, and cocktail effect. [40][41][42] The high-entropy effect leverages the enhanced compatibility between elements due to high mixing entropy, facilitating the formation of solid solutions and providing exceptional stability. The electron interaction among the multiple elements uniformly dispersed within the material supplies the necessary binding energy for reaction intermediates, resulting in reduced overpotential in 2D HEAs.…”
Section: Introductionmentioning
confidence: 99%